Estimation of hysteretic losses for MgB2 tapes under the operating conditions of a generator. (2nd February 2016) - Vargas-Llanos, Carlos Roberto; Zermeño, Víctor M R; Sanz, Santiago; Trillaud, Frederic; Grilli, Francesco
Abstract: Hysteretic losses in the MgB2 wound superconducting coils of a 550 kW synchronous hybrid scaled generator were estimated as part of the European project SUPRAPOWER led by the Spanish Fundación Tecnalia Research & Innovation. Particular interest was given to the losses caused by the magnetic flux ripples in the rotor coils originating from the conventional stator during nominal operation. To compute these losses, a 2D finite element analysis was conducted and Maxwell's equations written in the H -formulation were solved considering the nonlinear material properties of the conductor materials. The modeled tapes are made of multiple MgB2 filaments embedded in a Ni matrix and soldered to a high purity copper strip and insulated with Dacron braid. Three geometrical models of single tape cross sections of decreasing complexity were studied: (1) the first model reproduced closely the actual cross section obtained from tape micrographs. (2) The second model was obtained from the computed elasto-plastic deformation of a round Ni wire. (3) The third model was based on a simplified cross section with the superconducting filaments bundled in a single elliptical bulky structure. The last geometry allowed the validation of the modeling technique by comparing numerical losses with results from well-established analytical expressions. Additionally, the following cases of filament transpositions of the multi-filamentary tape were studied: no transposition, partial and full transposition; thereby improving understanding of the relevance of the tape fabrication process on the magnitude of the determination of ac losses. Finally, choosing the right level of geometrical detail, the following operational regimes of the machine and its impact on individual superconducting tape losses in the rotor were studied: bias-dc current, ramping current under ramping background field and magnetic flux ripples under dc background current and field.